Folklore and It’s Effect on Student’s Ability In Reading Narrative Text: a Systematic Literature Review - Irma Suryani; Misrita Misrita; Ristati Ristati (Indonesian Language Education and Literature, 2021)
This study describes the improvement of narrative text reading skills using folklore. The method used is a systematic literature review (SLR). This article provides a systematic review of journals discussing folklore in reading narrative texts. Search using Google Scholar, Science Direct.com, and JSTOR for ten years (2011-2021). After being selected, observation found ten articles to be eligible for analysis. The results showed that folklore could significantly improve students' ability to read narrative texts.Penelitian ini bertujuan untuk mendeskripsikan peningkatan keterampilan membaca teks narasi dengan menggunakan cerita rakyat. Metode yang digunakan adalah systematic literature review (SLR). Artikel ini memberikan tinjauan sistematis terhadap jurnal yang membahas penggunaan cerita rakyat dalam membaca teks naratif. Pencarian menggunakan Google Scholar, Science Direct.com, dan JSTOR selama sepuluh tahun (2011-2021). Setelah diseleksi, sepuluh artikel yang ditemukan memenuhi syarat untuk dianalisis. Hasil penelitian menunjukkan bahwa penggunaan cerita rakyat secara signifikan dapat meningkatkan kemampuan siswa dalam membaca teks naratif.